Safety and immunogenicity of seasonal trivalent inactivated influenza vaccines in pregnant women. Issue 52 (18th December 2018) - Munoz, Flor M.; Jackson, Lisa A.; Swamy, Geeta K.; Edwards, Kathryn M.; Frey, Sharon E.; Stephens, Ina; Ault, Kevin; Winokur, Patricia; Petrie, Carey R.; Wolff, Mark; Patel, Shital M.; Keitel, Wendy A
Abstract: Background: In the United States, seasonal inactivated influenza vaccine (IIV) is recommended for pregnant women; however, in early 2009, immunization rates were low, partly due to limited prospective data and concerns about vaccine safety. Objective: We conducted a randomized study of two licensed seasonal trivalent IIVs (IIV3) to assess their safety and immunogenicity in pregnant women. Study Design: In this prospective, randomized clinical study, 100 pregnant women, 18–39 years of age and ≥14 weeks gestation received a single intramuscular dose of 2008–2009 Fluzone® or Fluarix®. Injection site and systemic reactions were recorded for 7 days after vaccination and serious adverse events (SAEs) and pregnancy outcomes were documented. Serum samples collected before and 28 days after vaccination were tested for hemagglutination inhibition (HAI) antibody levels. Results: The majority of the injection site and systemic reactions were mild and self-limited after both vaccines. No fever ≥100 °F was reported. There were no vaccine-associated SAEs. Immune responses to influenza vaccine antigens were similar for the two study vaccines, with robust HAI responses against influenza A strains, and relatively lower responses for influenza B strains. Conclusion: Seasonal inactivated influenza vaccines were well tolerated and immunogenic in pregnant women. ClinicalTrials.gov identifier NCT00905125. Synopsis: In this prospective clinical trial, we demonstrated that immunization with seasonal trivalent, inactivated influenza vaccine in the second and third trimester of pregnancy is immunogenic and safe.